Synthesis and photocatalytic activity of TiO2 on phenol degradation: DOI: 10.48129/kjs.13509 - Permana, Muhamad Diki; Noviyanti, Atiek Rostika; Lestari, Putri Rizka; Kumada, Nobuhiro; Eddy, Diana Rakhmawaty; Rahayu, Iman (Kuwait Journal of Science, 2022)
Photocatalysis has the ability to degrade phenols into other compounds which are relatively non-toxic to the environment. Titanium dioxide (TiO2) is one of the most widely developed photocatalysis materials, and is used because of its high catalytic activity, stability and very affordable. The most commonly used precursors of TiO2 are titanium butoxide (TBOT) and titanium tetraisopropoxide (TTIP). These variations in precursor can lead to phase difference in the formation of TiO2 crystals, which further improves its nature in the activity of photocatalysis. In this study, the sol-gel method was used to synthesize titanium dioxide nanoparticles from variations of TBOT and TTIP. Futhermore, the structure, crystallite size and bandgap of TiO2 were determined by X-ray diffraction (XRD) and UV-vis reflectance spectroscopy (DRS). Subsequently, TiO2 photocatalytic activity was evaluated in phenol photodegradation as a contaminant model with UV irradiation. The results showed the structure synthesized from TBOT had a higher amount of anatase, higher crystallinity, smaller crystallite size, larger bandgap, and better photocatalytic activity than those from TTIP. Futhermore, it was shown that TiO2 from TBOT had an efficiency of 147% greater than TiO2 P25 Degussa, while TiO2 from TTIP had 66% efficiency compared to TiO2 P25.